2018
DOI: 10.1209/0295-5075/124/30004
|View full text |Cite
|
Sign up to set email alerts
|

Velocity alignment promotes motility-induced phase separation

Abstract: We study the phase behavior of polar Active Brownian Particles moving in twospatial dimensions and interacting through volume exclusion and velocity alignment. We combine particle-based simulations of the microscopic model with a simple mean-field kinetic model to understand the impact of velocity alignment on the motility-induced phase separation of selfpropelled disks. We show that, as the alignment strength is increased, approaching the onset of collective motion from below, orientational correlations grow,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…More recently MIPS has also seen for circle swimmers 49,50 and more complicated aligning interactions 51,52 . This shows that the occurence of MIPS itself is a very robust and general effect.…”
Section: Collective Effects Of Active Brownian Particles: Mipsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently MIPS has also seen for circle swimmers 49,50 and more complicated aligning interactions 51,52 . This shows that the occurence of MIPS itself is a very robust and general effect.…”
Section: Collective Effects Of Active Brownian Particles: Mipsmentioning
confidence: 99%
“…More studies on MIPS including a non-vanishing moment of inertia and an external torque will be performed. The role of aligning interactions needs to be understood better for inertial systems 87,88 . Active crystallization will be studied where inertia provides a latent heat upon crystallization.…”
Section: Perspectivesmentioning
confidence: 99%
“…Precisely this inverse effect was reported earlier in Refs. [17,18]: MIPS is enhanced for self-propelled particles that align through Vicsek interactions. In binary collisions, the Vicsek torques always rotate particles towards the combined center of mass, increasing the duration of collisions, increasing hindrance and thus enhancing MIPS.…”
Section: B Torque-induced Suppression Of Motility-induced Phase Sepamentioning
confidence: 99%
“…Studies that do include torques typically fall into two categories. The first uses particles with Vicsek-like alignment interactions [17,18], which mimic a visual alignment mechanism, such as for birds or fish. The second uses particles with an anisotropic, typically rodlike shape [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon, known as Motilityinduced Phase Separation (MIPS) has been largely investigated [40], starting from the pioneering work of Fily and Marchetti [41]. The coexistence of clustering and velocity ordering has been recently considered, and, even if its role in MIPS is still an open question [42][43][44][45], it has been shown that may induce freezing in dense regimes [46]. The alignment, characterizing Vicsek-like models [47], and the ABP phase-separation are phenomena which are usually thought to be generated by two distinct types of interactions between particles.In the present study, we challenge the widespread idea that explicit alignment interactions are necessary to observe a growing orientational order or -equivalently -that the velocity alignment observed in Vicsek-like models do not appear in purely repulsive, spherical ABP particles.…”
mentioning
confidence: 99%